Long-term efficacy and safety of hydroquinidine in patients with Brugada syndrome. (25th November 2020) - Angelini, F; Pourshayesteh, S; Gastino, E; Cingolani, M.M; Castagno, D; Cerrato, N; Gaita, F; De Ferrari, G.M; Giustetto, C
Abstract: Background: Brugada syndrome (BrS) is an inherited channelopathy with an increased risk of supraventricular, ventricular arrhythmias (VAs) and sudden cardiac death (SCD). Implantable cardioverter-defibrillator (ICD) is a cornerstone of SCD prevention, but it does not reduce the incidence of life-threatening VAs and it can carry substantial complications. Hydroquinidine (HQ) is a class IA antiarrhythmic drug used for electrical storms, to reduce ICD's appropriate discharges and as an alternative to ICD in children with BrS or in patients with a contraindication to ICD. Nevertheless, HQ's side effects may undermine treatment compliance. Purpose: The aim of this study was to evaluate the efficacy and safety of HQ in reducing VAs (ventricular fibrillation, sustained and non-sustained ventricular tachycardia) inducibility at electrophysiology study (EPS) and atrial fibrillation/flutter (AF/AFL) or VAs recurrence in patients with BrS. Methods: From the prospective Piedmont Brugada Registry, patients treated with HQ were selected and divided into three groups according to the indication for HQ initiation: index EPS positive for VAs induction (group 1), secondary prevention of AF/AFl (group 2), secondary prevention of VAs (group 3). In group 3 recurrence of VAs was monitored by implantable devices or by periodic 24-hour ECG Holter monitoring. In 5 patients HQ was started for reasons different from the above mentioned, so they were considered only for safety outcomes. Safety was assessed considering the occurrence of HQ side effects and their impact on treatment discontinuation. Results: A total of 98 patients (79 males, 80, 6%) were included. Median follow-up was 61 months (IQR 31–89 months). None of the baseline clinical characteristics was associated with arrhythmic recurrences. Among 46 patients in group 1 HQ was effective in reducing EPS inducibility in 91.9% of patients (p<0.0001); in group 2 (31 patients) HQ reduced palpitations [before HQ 83, 8%, with HQ 27, 6%, RRR 67.1%, NNT 1.8; p<0.0001] and no AF/AFL recurrence was recorded during follow-up (p<0.0001); in group 3 (17 patients; 70.6% with ICD/LR implanted) VAs recurrences were significantly reduced in patients with HQ (5.9% recurrence rate, p<0.0001). Overall, no cardiac arrest occurred during follow-up. At ECG, HQ determined a significant increase in QTc duration (V5-lead mean QTc duration pre-HQ 406 ms vs with HQ 428 ms; p=0.001). Overall, 28.6% of patients presented HQ-related side effects, mainly due to gastrointestinal intolerance (18.3%). Treatment discontinuation rate was 25% but only about half of these patients discontinued HQ for adverse events (29.2% for GI intolerance, 16.7% for drug-induced QTc prolongation, 8.3% for elevated liver enzymes; 45.8% self-discontinuation). Conclusions: In patients with BrS, HQ was effective in reducing VAs inducibility at EPS, AF/AFL and VAs recurrences; moreover, it was effective in reducing symptoms. Overall, HQ proved to be safe and well-tolerated. Funding Acknowledgement: Type of funding source: None